Bimodality & the performance of PPML - Sören Prehn; Bernhard Brümmer (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2012)
There has been an extensive discussion on the applicability of Poisson Pseudo Maximum Likelihood (PPML) to trade. Here, we are going to analyse again the performance of PPML but in the light of a bimodal distribution; in addition, we also explicitly account for excess zeros. Simulations are based on a Bernoulli-Gamma distribution (a zero-inflated Gamma distribution). Again, our results are a confirmation of how well-behaved PPML is in general.
Keywords: 330; Poisson Pseudo Maximum Likelihood; excess zeros; zero-inflated Gamma Distribution; simulation; Maximum-Likelihood-Methode; Statistische Verteilung; Simulation; Außenwirtschaft; Gravitationsmodell; Theorie